ESWT as treatment of extensor tendinopathy of the elbow: prognostic value of ultrasonography - Maroy, M. F. Y. P.; van den Eede, E.; Peers, K. (Medicine and Science in Tennis, 2007)
The objective of this study was to determine if ultrasonography has a prognostic value for the outcome of ESWT (Extracorporal ShockWave Therapy) in the treatment of the extensor tendinopathy of the elbow. Following the results of the study it was concluded, that Ultrasonography has potential prognostic value to predict the outcome of ESWT treatment in patients with extensortendinopathy of the elbow. More prospective studies should be done, with larger patient subgroups, to confirm this statement.